Development and implementation of PROgmatic: A clinical trial management system for pragmatic multi-centre trials, optimised for electronic data capture and patient-reported outcomes. (June 2014) - Cramon, Per; Rasmussen, Åse Krogh; Bonnema, Steen Joop; Bjorner, Jakob Bue; Feldt-Rasmussen, Ulla; Groenvold, Mogens; Hegedüs, Laszlo; Watt, Torquil
Background: Many clinical trials are conducted as explanatory trials, but the applicability of results from explanatory trials to clinical practice may be questioned. Pragmatic trials elucidate both benefits and harms of an intervention under conditions close to daily clinical practice. We have planned a pragmatic multi-centre trial in patients with Graves' hyperthyroidism. However, trial management is a complicated task in pragmatic trials, due to limited interaction between participants and trial personnel. Purpose: The aim of this project was to develop and implement PROgmatic, a fully integrated trial management system for pragmatic multi-centre trials, optimised for electronic data capture and patient-reported outcomes (PROs). Methods: Necessary tasks and logistical challenges that should be handled by PROgmatic were identified, and the system was designed and developed to handle these tasks. A combination of generic applications and custom coding was applied to develop an integrated system that met the required needs. PROgmatic features include secure web-based data entry; electronic case report forms (eCRFs); central participant registration and randomisation; automated emails linking to electronic PROs; automated reminders to participants; automated notifications to trial personnel regarding booking of trial visits, safety and compliance alerts; and monitoring of trial progress. PROgmatic underwent rigorous pilot testing, including data verification and validation, before it was released for trial management. Results: PROgmatic was successfully implemented in the GRAves' Selenium Supplementation (GRASS) trial (ClinicalTrials.gov: NCT01611896) December 2012. The feedback from trial personnel on usability and utility has been positive, and PROgmatic has handled all intended tasks properly. Limitations: Implementation of PROgmatic in future studies requires adaptation of the custom coding. Not all email systems accept emails with active links, and participants who use these systems therefore need to complete paper surveys. Conclusions: PROgmatic facilitated the complex task of conducting a pragmatic multi-centre trial. The automated electronic capture of PRO data is time saving and reduces the risk of erroneous data entry. Email notifications to trial personnel combined with serially activated eCRFs that logically lead patient flow through the trial have helped making the pragmatic trial feasible. PROgmatic provides a template for other pragmatic multi-centre trials with patient-reported measures as high-priority outcomes.